Education quality, and teaching and learning in the post-2015 education agenda. (January 2015) - Sayed, Yusuf; Ahmed, Rashid
Highlights: Analysis of UNESCO consultation on the post-2015 education agenda. A risk of the post-2015 agenda is that education quality is still being defined as literacy, numeracy, and still being constrained by what can be measured. There is a failure in the post-2015 agenda to engage more broadly with teaching and learning as well as the diverse contexts of teaching and learning. A dynamic, process oriented social justice approach to education quality is needed. Abstract: At present, there is an intense and wide-ranging debate on the future of global development. This debate occurs in a context of increasing global inequality, global economic recession, conflict, and climate change. Discussions about the post-2015 education and development agenda in this context ambitiously seek to eradicate poverty, promote social and economic inclusion, tackle climate change, promote equity, and access to quality education. While the exact goals are not yet agreed and the shape of the final post-2015 development is still to be settled, there is a widespread consensus that education is priority and that equitable and quality education is core to the agenda. In this context, this paper discusses the continuities and discontinuities in the proposed post-2015 quality agenda through a textual analysis of UNESCO consultations on Education for All (EFA). In particular, this article focuses on the UNESCO post-2015 position paper and the Muscat Global Education meeting agreement in April 2015. They are significant policy texts as they evidence the current global education discourse on education and the development agenda and reflect the broad consultations and thinking reflected in the thematic consultations. They also are important as they seek to clarify and secure the focus on the Education for All goals within a future post-2015 development agenda. The analysis of these texts pays particular attention to how quality is conceptualised in these texts, how it is translated into targets and how teachers are located in the global education quality discourse. The paper argues that while potentially broad conceptualisations of quality emerge from these texts, quality is still being defined as literacy and numeracy and still being constrained by what can be measured. While teachers are identified as crucial to the quality agenda, there is still a failure to engage more broadly with teaching and learning as well as the diverse contexts of teaching and learning. The article argues that what is needed is a continued foregrounding of quality as a dynamic, process oriented social justice endeavour to give effect to a holistic and comprehensive approach to the broad quality agenda.